Using the Practical, Robust Implementation and Sustainability Model to identify implementation determinants of a statewide diabetes learning collaborative in Kentucky - Aaron J. Kruse-Diehr; Borsika A. Rabin; Jessica Elliott; Vance Drakeford; Laura Wright; Brent McKune; Russell E. Glasgow; Key C. Douthitt; James W. Keck; Mary E. Lacy (BMC Health Services Research)
Abstract Background Prevalence of type 2 diabetes (T2D) in Kentucky is among the highest in the United States. Diabetes self-management education and support (DSMES) is an evidence-based intervention that teaches people living with T2D to self-manage their disease but is underutilized in Kentucky despite being available free-of-charge to residents of every county. One promising strategy to improve DSMES utilization is clinic participation in a learning collaborative, wherein participants undertake small tests of change to improve the referral process. The purpose of this study was to identify determinants related to successful implementation of the learning collaborative, as well as perceived progress on implementation outcomes, as experienced by previous collaborative participants. Methods Semi-structured Zoom interviews were conducted with three discrete groups of learning collaborative participants (N = 26): (1) clinic practitioners and support staff (n = 13); (2) health department educators (n = 8) who received DSMES referrals from clinics; and (3) staff of a regional extension center (n = 5) who facilitated the collaboratives. Questions were aligned with Practical, Robust Implementation and Sustainability Model (PRISM) domains, and responses were transcribed verbatim. Data were coded using a matrix-based approach, with codes grouped into overarching themes within each domain to describe salient determinants. Results Participants most frequently identified facilitators and barriers aligned with the PRISM domains of organizational perspectives on intervention, organizational and patient characteristics, and implementation and sustainability infrastructure. Multiple strategies and adaptations were used throughout implementation to leverage strengths and mitigate barriers. For example, whereas clinic participants identified competing priorities, such as reporting requirements, as an infrastructure barrier, they successfully utilized morning huddles to ensure collaborative goals were met. Conclusions Data from this study provided context for determinants that positively and negatively impacted implementation of the collaborative, as well as strategies used by implementers to address these determinants. These data will be used to refine the collaborative and select responsive implementation strategies to address identified barriers for an upcoming cohort of clinic participants in which we will evaluate this framework as a model for increasing referrals to, and engagement with, DSMES among patients living with diabetes from two healthcare systems in Appalachia Kentucky.